Development of a loop-mediated isothermal amplification (LAMP) assay for rapid and specific detection of common genetically modified organisms (GMOs). (March 2015) - Feng, Jiawang; Tang, Shiming; Liu, Lideng; Kuang, Xiaoshan; Wang, Xiaoyu; Hu, Songnan; You, Shuzhu
Abstract Here, we developed a loop-mediated isothermal amplification (LAMP) assay for 11 common transgenic target DNA in GMOs. Six sets of LAMP primer candidates for each target were designed and their specificity, sensitivity, and reproductivity were evaluated. With the optimized LAMP primers, this LAMP assay was simply run within 45–60 min to detect all these targets in GMOs tested. The sensitivity, specificity, and reproductivity of the LAMP assay were further analyzed in comparison with those of Real-Time PCR. In consistent with real-time PCR, detection of 0.5% GMOs in equivalent background DNA was possible using this LAMP assay for all targets. In comparison with real-time PCR, the LAMP assay showed the same results with simple instruments. Hence, the LAMP assay developed can provide a rapid and simple approach for routine screening as well as specific events detection of many GMOs.